Taxonomic notes on the genus Millettia (Fabaceae: Millettieae) in Vietnam - Song, Zhu-Qiu; Li, Shi-Jin; Vu, Quang Nam; Khang, Nguyen Sinh (Phytotaxa, 2022)
Millettia is a complex genus of the tribe Millettieae (Fabaceae). In this paper we provide a synopsis of the species of the genus from Vietnam, based on the examination of literature and specimens as well as field surveys. Millettia boniana and M. setigera are proposed as new synonyms of Derris tonkinensis and M. cubittii, respectively. Millettia densiflora, a species most recently described from Laos, is newly reported in central and southern Vietnam. Millettia acutiflora is treated under the newly reinstated genus Imbralyx as I. acutiflorus. Twelve species and one variety are excluded from the list of Vietnamese species of Millettia. As a result, fourteen species and one variety of Millettia are recognized in Vietnam. A key to the species and lectotypification for seventeen names are provided.